c-Myc Inhibition Induces an Additive Effect with Cyclophosphamide in Acute Lymphoblastic Leukemia - Mohammad Sadeghi; Maryam Panahi; Zahra Kheyrizadeh; Leili Aghebati-Maleki; Ali Akbar Movasaghpour Akbari; Abbas Ali Hosseinpour Feizi; Sima Shahmohammadi Farid; Sanam Dolati; Farhad Jadidi-Niaragh (ImmunoAnalysis)
Background: Cellular-myelocytomatosis (c-Myc), an oncoprotein and a transcription factor, is involved in several essential cellular processes. The c-Myc expression level is highly regulated in normal cells. It has been proved that c-Myc expression is deregulated in malignant cells due to rearrangements and mutations. The overexpression of this molecule is also reported to be present in acute lymphoblastic leukemia (ALL) as well, which is correlated with an unfavorable response to treatment, poor prognosis, and decreased overall survival. The upregulation of c-Myc results in increased proliferation, cell growth, and survival of ALL cells. Hence, making it an ideal target for leukemia treatment. This study evaluates the effect of c-Myc silencing combined with cyclophosphamide treatment, an FDA-approved chemotherapeutic. Methods: Peripheral blood and bone marrow samples (mononuclear cells) were derived from eleven ALL patients. To silence c-Myc, small interfering-RNA (siRNA)-lipofectamine was used. The efficacy of gene silencing was assessed by the qRT-PCR test. Next, the effect of c-Myc silencing combined with cyclophosphamide treatment in ALL primary cells was evaluated using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) test. Results: ALL cells were successfully transfected with c-Myc-siRNA. Also, treating cells with cyclophosphamide exerted a slight fall in the c-Myc mRNA level. The MTT test revealed that following the inhibition of c-Myc by siRNA, the viability of primary ALL cells decreased in response to cyclophosphamide treatment. Also, it was discovered that silencing c-Myc with siRNA combined with cyclophosphamide treatment significantly inhibits the growth of primary ALL cells compared to cyclophosphamide monotherapy. Conclusion: c-Myc possesses high potential in the treatment of several cancers. Our findings add ALL to this category as well. Silencing c-Myc sensitizes ALL cells to cyclophosphamide treatment and can help with the better treatment of the afflicted individuals.